Effective Bug Triage Using Cold-Start Recommendation System - Alle, Rajusekhar; Aranya, Aditya; Thakur, Abhishek; J Kadam, Mr. Anilkumar (IJRDO -Journal of Computer Science Engineering, 2016)
Over 40-50% cost is spent in dealing with software bugs in Software companies. Aninevitable step of fixing bugs is bug triage, which aims to correctly assign a developerto a new bug. To decrease the time cost in manual work, text classification techniquesare applied to implement automatic bug triage. A system can be constructed which willaddress the problem of data reduction for bug triage, i.e., how to reduce the scale andimprove the quality of bug data. A combination of instance selection and featureselection can be used simultaneously to reduce data scale on the bug dimension and theword dimension. And this system will solve the Cold-Start Problem encountered in thecurrent system at the starting phase when there is no trained dataset and this systemwill use designation-matching.